Application of Shopping Bag to Consumer Green Purchase Behavior Through Green Trust, and Green Perceived Value - Adrie Charviandi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2023)
The success of government policies in inviting the public and industry to be environmentally conscious at the level of use and produce very high environmentally friendly plastic bags in their daily lives needs to be studied further in a study on Green Purchase Behavior. This study aims to determine the effect of green perceived value on consumers' eco-friendly buying behavior using shopping bags, and the effect of green trust on green purchase behavior of consumers to use eco-friendly shopping bags in modern markets and traditional markets in the city of Jakarta. The research was conducted at modern and traditional markets in the city of Jakarta using 240 respondents who shopped at modern and traditional markets. A model to measure eco-friendly purchasing behavior with reusable shopping bags using two interrelated variables, namely: Green Perceived Value and Green Trust. Data analysis using Structural Equation Modeling (SEM). The results of the analysis and discussion show that green perceived value has a positive and significant effect on green purchase behavior, while green trust has a positive and significant effect on green purchase behavior.